CRISPR-Cas9; an efficient tool for precise plant genome editing. (June 2018) - Islam, Waqar
Abstract: Efficient plant genome editing is dependent upon induction of double stranded DNA breaks (DSBs) through site specified nucleases. These DSBs initiate the process of DNA repair which can either base upon homologous recombination (HR) or non-homologous end jointing (NHEJ). Recently, CRISPR-Cas9 mechanism got highlighted as revolutionizing genetic tool due to its simpler frame work along with the broad range of adaptability and applications. So, in this review, I have tried to sum up the application of this biotechnological tool in plant genome editing. Furthermore, I have tried to explain successful adaptation of CRISPR in various plant species where it is used for the successful generation of stable mutations in a steadily growing number of species through NHEJ. The review also sheds light upon other biotechnological approaches relying upon single DNA lesion induction such as genomic deletion or pair wise nickases for evasion of offsite effects. Highlights: CRISPR-Cas9 mechanism is a revolutionizing tool due to is simpler frame work and broad adaptability. This review embeds the application of this biotechnological tool in plant genome editing. Successful adaptation of CRISPR-Cas9 in various plant species for generation of stable mutations is highlighted. Biotechnological approaches relying upon single DNA lesion induction for evasion of offsite effects have been explained as well.